ANSWER
![y = \cot(x - (\pi)/(3) ) + 2](https://img.qammunity.org/2020/formulas/mathematics/college/n5epy4rfwdzwjmdvytooykh1uqbdymi6pa.png)
Step-by-step explanation
The cotangent function that is fully transformed is of the form
![y =a \cot(bx + c) + d](https://img.qammunity.org/2020/formulas/mathematics/college/a1x3eizhrhzpegzqy6tncycgko1zobw869.png)
where 'a' is the amplitude.
![(\pi)/(b) = \pi](https://img.qammunity.org/2020/formulas/mathematics/college/w8pbwuoy5hyl9j2rerfbtdphdjz7sud0mn.png)
is the period.
This implies that b=1
The phase shift is
![(c)/(b) = - (\pi)/(3)](https://img.qammunity.org/2020/formulas/mathematics/college/vv4ftbcrcmtgh1poy5udn6ifivf96qtaqr.png)
Substitute b=1 to get;
![c = - (\pi)/(3)](https://img.qammunity.org/2020/formulas/mathematics/college/ulewpiux6ok0tun1yslgizcl99d8gpf5e7.png)
and d=2 is the vertical shift.
We choose a=1 to get the required function as
![y = \cot(x - (\pi)/(3) ) + 2](https://img.qammunity.org/2020/formulas/mathematics/college/n5epy4rfwdzwjmdvytooykh1uqbdymi6pa.png)